2020
DOI: 10.21203/rs.3.rs-45988/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dosimetric comparison of helical tomotherapy, volume-modulated arc therapy, and fixed-field intensity-modulated radiation therapy in nasopharyngeal and cervical cancers

Abstract: Background: To compare the dosimetric parameters of different radiotherapy plans, helical tomotherapy(HT), volume-modulated arc therapy (VMAT), and fixed-field intensity-modulated radiation therapy (FF-IMRT) for nasopharyngeal carcinoma (NPC) and cervical cancer (CC).Methods: A total of 15 patients with NPC and 15 patients with CC were chosen for retrospective analysis and replanned for HT, VMAT, and FF-IMRT. The prescribed doses of the planning target were 2.12/69.96 Gy, 1.8/59.4 Gy for NPC and 1.8/45 Gy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…HT plans reduced the maximum doses of most organs such as brainstem, spinal cord, and optic nerves in NPC and significantly reduced the volume of high dose region. 20 Study by Liu et al, in the treatment of locally advanced NPC by HT showed that HT can achieve promising disease control and survival in the treatment of locally advanced NPC patients with mild acute and late toxicity profiles. 21 Limitation of our study was smaller sample size and possible interpersonal variation in contouring.…”
Section: Discussionmentioning
confidence: 99%
“…HT plans reduced the maximum doses of most organs such as brainstem, spinal cord, and optic nerves in NPC and significantly reduced the volume of high dose region. 20 Study by Liu et al, in the treatment of locally advanced NPC by HT showed that HT can achieve promising disease control and survival in the treatment of locally advanced NPC patients with mild acute and late toxicity profiles. 21 Limitation of our study was smaller sample size and possible interpersonal variation in contouring.…”
Section: Discussionmentioning
confidence: 99%